Spectroscopic characterization of schiff base-copper complexes immobilized in smectite clays - Dias, Patrícia M.; Kinouti, Lilian; Constantino, Vera R. L.; Ferreira, Ana M. D. C.; Gonçalves, Marcos B.; Nascimento, Rafael R. do; Petrilli, Helena M.; Caldas, Marília; Frem, Regina C. G. [UNESP] (Sociedade Brasileira de Química, 2010)
Herein, the immobilization of some Schiff base-copper(II) complexes in smectite clays is described as a strategy for the heterogenization of homogeneous catalysts. The obtained materials were characterized by spectroscopic techniques, mostly UV/Vis, EPR, XANES and luminescence spectroscopy. SWy-2 and synthetic Laponite clays were used for the immobilization of two different complexes that have previously shown catalytic activity in the dismutation of superoxide radicals, and disproportionation of hydrogen peroxide. The obtained results indicated the occurrence of an intriguing intramolecular redox process involving copper and the imine ligand at the surface of the clays. These studies are supported by computational calculations.
Keywords: Schiff base-copper complexes; smectite clays; DFT calculation